Defining and measuring subjective well-being for sport policy. Issue 4 (2nd October 2018) - Testoni, Stefano; Mansfield, Louise; Dolan, Paul
ABSTRACT: This paper makes the case for assessing the value of sport based on people's reports of subjective well-being (SWB), i.e. how they feel. We compare SWB to conventional definitions of well-being. We discuss how SWB is measured, distinguishing between evaluations (e.g. life-satisfaction) and experiences (feelings held moment to moment). We then consider evidence on the impact of sport on both evaluations and experiences of SWB, showing that the two give rise to different insights. We argue that measures that focus on how people feel as they go about their lives are better suited to account for the value of sport. We conclude by encouraging the measurement of experiences of SWB in sport policy.